STEM CRUSHING - AN ECO-FRIENDLY WAY TO EFFECT ON FLAX DEW-RETTING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Preparation of flax raw material - retted straw - is becoming more and more problematical since the straw is prepared by way of dew-retting, because this run under the open sky and fully couldn’t be controlled, and this concludes in insufficient fibre quality. Besides of this, during the flax pulling process part of the stems is caught by the belts of the pulling combine LKV-4T and consequently is damaged (crushed). Thus fibre separation in this part of the stem usually runs more quickly and the quality of flax fibre along the stem becomes uneven. Top-part of the stem is damaged by thrashing apparatus. Furthermore, we should remember that the shape offlax stem is a cone, and dew-retting process at flax foot part takes much longer than at the top or at the strongly damaged middle part of the stem. The influence of crushing of fibre flax stems and desiccation was investigated at the Upyte Research Station of LIA in 2003. Special crushing apparatus was assembled on the flax combine LKV-4T. Desiccated with glyphosate and non-desiccated flax stems were crushed during pulling. The quality of fibre after stem crushing was higher.